2009
DOI: 10.1111/j.1600-0625.2009.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by a novel, dissociated Vitamin D3 analogue

Abstract: The biologically active metabolite of vitamin D3, 1alpha,25-dihydroxyvitamin D3, has potent immunomodulatory activity; however, its clinical use is limited because of its hypercalcaemic activity in anti-inflammatory active doses. Here, we present ZK203278, a novel, structurally different vitamin D3 analogue with profound immunomodulatory activities. It potently inhibits lymphocyte proliferation in the mixed lymphocyte reaction, and release of cytokines that are central in inflammation, such as TNFalpha and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…Vitamin D in particular has been the subject of intensive research, both in its mechanism of action and its effects on various human neoplasms [6, 7, 11, 18, 2325]. Multiple studies have demonstrated that vitamin D can affect the rate of proliferation, degree of apoptosis, and the phenotype of numerous neoplastic cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D in particular has been the subject of intensive research, both in its mechanism of action and its effects on various human neoplasms [6, 7, 11, 18, 2325]. Multiple studies have demonstrated that vitamin D can affect the rate of proliferation, degree of apoptosis, and the phenotype of numerous neoplastic cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve such concentrations in vivo requires supra‐physiological doses of 1,25(OH) 2 D3, which are associated with the undesired risk of hypercalcaemia. Consequently, novel therapeutic strategies point toward vitamin D analogues that do not induce hypercalcaemia, 142 which may exert considerable immunomodulatory activity at non‐hypercalcaemic dosages and may have therapeutic potential for immune disorders or transplant rejection. In patients with Crohn’s disease a vitamin D analogue activates VDR in PBMCs, affecting proliferation and exerting an immunosuppressive effect on tumour necrosis factor‐α production, which is mediated by NF‐κB down‐regulation 143 .…”
Section: Further Directions and Concluding Remarksmentioning
confidence: 99%
“…Here, we analyzed the impact of a recently described low‐calcemic VDR agonist (14) on the activation of different B cell subsets. Our results show that VDR activation inhibits IgE and IgG, but also IgA to a lesser extent.…”
mentioning
confidence: 99%